Social cohesion in New Zealand. Background paper to Te Tai Waiora: Wellbeing in Aotearoa New Zealand 2022 - Craig Fookes (New Zealand Government, The Treasury, 2022)
This report discusses the evidence base relating to social cohesion in New Zealand. It introduces the relevant concepts and reviews cohesion indicators for New Zealand, including those used in theLiving Standards Framework Dashboard.
Keywords: 330; Sozialkapital; Soziale Lage; Soziale Beziehungen; Soziale Integration; Neuseeland